Factors affecting the creaming of human milk. (September 2020) - Meng, F.; Uniacke-Lowe, T.; Lanfranchi, E.; Meehan, G.; O'Shea, C.A.; Fox, P.F.; Huppertz, T.; Ryan, C.A.; Kelly, A.L.
Abstract: The creaming properties of human milk have not been widely studied to date, and a mechanism for this phenomenon is not known. Here, the natural creaming of human milk, as affected by temperature and pre-treatments, was studied using dynamic light-scattering. The creaming rate of human milk increased with temperature in the range 5 °C–40 °C. Freezing human milk at −20 °C and thawing at room temperature had little influence on creaming. Compared with bovine milk, human milk showed a faster creaming rate at 40 °C, but a slower rate at 5 °C, suggesting a lack of cold agglutination; the mechanisms of creaming were also shown to differ in response to heat treatment. This study expands the current knowledge on milk creaming, and may have potential application to storage and handling of human milk in hospitals or homes, therefore supporting optimal nutrition of infants.